Mobility in the age of massive data: opportunities and challenges - Ferreira, Douglas; Lucas, Fabricio; Gonçalves, José; Kassio, Pedro; Oliveira, Samuel; Aurelio, Yuri; Bergamo, Gustavo; Born, Paulo; Ciarlini, Angelo (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2022)
The development of IoT and machine learning in recent years has brought new opportunities to the mobility industry. The amount of data collected from the fleet with telemetry is not only more accurate but also more available with lower IoT costs. Customers’ experience and profitability can be dramatically improved by means of using IoT datasets and machine learning models. These opportunities however come together with Big Data challenges. In this paper, we describe some of the opportunities and challenges that Localiza, the largest car rental company in Brazil, has been addressing as part of its digital transformation.